Diaphragmatic hernia during treatment of lung cancer harboring an EGFR mutation - Konno-Yamamoto, Aya (Oxf Med Case Reports, 2021)
Epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors (TKIs) are a first-line treatment for patients with nonsmall-cell lung cancer harboring EGFR mutations. We report a 65-year-old Japanese woman with nonsmall-cell lung cancer taking an EGFR-TKI who visited the emergency department with acute nausea and vomiting. Imaging studies demonstrated an incarcerated diaphragmatic hernia. Urgent diagnostic surgery revealed a gap in the diaphragm acting as a hernial orifice, where a metastatic tumor was detected. We consider that regression of the diaphragmatic metastasis by EGFR-TKI therapy resulted in perforation of the diaphragm, causing the diaphragmatic hernia. Gastrointestinal adverse events, e.g. nausea, vomiting and diarrhea, are common during EGFR-TKI treatment. However, this case suggests that in patients with diaphragmatic metastasis, we should consider the rare possibility of diaphragmatic perforation and a subsequent hernia.